Penerapan Model Pembelajaran Proyek Based Learning Dalam Pembelajaran Menulis Teks Pidato Siswa Kelas VIII C Smp Nasional Sariputra Kota Jambi - Lovika, Indri; Dewi, Yusra; Rasdawita, Rasdawita (Universitas Batanghari Jambi, 2025)
This research aims to describe the application of the project based learning model in learning to write speech texts for class VIII C students of sariputra nasional middle school, Jambi city. This research was carried out at sariputra nasiona middle school Jambi city. This research was carried out at sariputra nasional middle school. The subject of this research was the Indonesian language teacher class VIII C at sariputra nasional middle school, Jambi city. The approach in this research is qualitative. This type of research is in the form of observations of teachers in implementing the project based learning model. The data obtained from this research is in the form of observations of teachers in implementing the project based learning model. The method used in this research is descriptive qualitative. Data collection techniques. The aspects assed in this research are the results of the Indonesian language teacher, namely Mrs. Widya Tri Rahayu, S. Pd. When implementing the project based learning model and the results of students’ work in learning to write speech texts. The results of this research show that the implementation of the project based learning model in learning to write speech texts for students in class VIII C of Sariputra Nasional middle school, Jambi city is implemented smoothly in accordance with the teaching module. This can be seen from the learning process starting when the teacher carries out preliminary activities, then at the core stage the teacher explains, asks questions and determines the results of the students’ work. Next, in the closing activity, the teacher and students conclude the learning that has been carried out